Persistent psychological distress in resettled refugee women-at-risk at one-year follow-up: Contributions of trauma, post-migration problems, loss, and trust. (April 2021) - Vromans, Lyn; Schweitzer, Robert D.; Brough, Mark; Asic Kobe, Mary; Correa-Velez, Ignacio; Farrell, Louise; Murray, Kate; Lenette, Caroline; Sagar, Vinita
The mental health of women has been largely neglected in the refugee literature, notwithstanding the specific gender-related issues that confront women seeking asylum. Furthermore, a specific category of women, deemed to be women-at-risk, face particular challenges in their journey and resettlement process. This longitudinal study investigated psychological distress in refugee women-at-risk one year after resettlement in Australia. Follow-up survey of 83 women-at-risk (mean age = 33.41 years; SD = 11.93) assessed: trauma events and symptoms; loss events and loss distress; level of post-migration problems; anxiety, depression, and somatic symptoms; and absence of trust in community members. Participants demonstrated no symptom change since initial assessment ( p > .05). Substantial proportions of women reported traumatization (39%), PTSD (20%), anxiety (32%), and depression (39%) above clinical cut-offs, and high levels of somatization and loss distress. Post-migration problems, trauma events, and region of birth were associated with all symptoms, with post-migration problems the strongest predictor. Absence of trust in community members was associated with trauma, depression, and somatic symptoms. Initial trauma and somatic symptoms were associated with follow-up traumatic and somatic symptoms. Loss and trauma events were associated with loss distress. Findings underline the role of post-migration problems on psychological distress and the need to consider women's psychological wellbeing in the context of their trauma and loss history, potential impacts of ethnicity, and complex socio-cultural dynamics underpinning issues of trust within communities. Effective service delivery requires that practitioners screen for and address psychological distress in women-at-risk at least up to 18 months after resettlement.